In-Service Teachers’ Perception of Continuing Education Programmes in Two African Universities - Olaniyi, Francis O.; Nzima, Dumisani R. (American International Journal of Social Science Research, 2019)
The study compared the in-service teachers’ perception of continuing education programmes from two universities in Africa; University of Zululand, South Africa (UZ), and Adekunle Ajasin University, Akungba-Akoko, Nigeria, (AAU). The study covers the impact, effectiveness and efficiency of UZ and AAU on in-service teachers’ of continuing education programmes. The target population and sample for the study were the current teachers of continuing education programmes of these universities. The instrument tagged ‘Questionnaire for Perceptions of Continuing Education Programmes by in-service Teachers’   (QPCEPIT) was designed and used for data collection. The descriptive survey research design of ex-post facto was adopted for the study. 150 questionnaires were randomly used for pilot study, carried out at Ekiti State University, Ado Ekiti, Nigeria, whilst 500 questionnaires each were administered at both UZ and AAU of which 365 and 321 responses were valid and analysed respectively. Four research questions were carefully formulated to ascertain the perceptions of continuing education programmes by in-service teachers in the selected universities. Inferential statistics was used to draw conclusions and test the research questions for the study. The results of the comparative study revealed that the conclusiveness of the learning environment, the nature and quality of student support services provided, the quality and learners’ perception of course modules or materials, accommodation problems and venue of the programme were the major predictors for motivation of in-service teachers of the programme. Based on the findings of the study recommendations were made on how the programme will have impact on the in-service teachers and how the universities that are running the programme will be effectively and efficiently manage the programme for the acceleration and advancement of socio-economic growth in South Africa, Nigeria, and the world at large.